PENGELOLAAN WAKAF TUNAI OLEH AZISWA DI PONDOK PESANTREN USHULUDDIN LAMPUNG SELATAN - Ahmad Alfikri (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2023)
Ushuluddin Islamic Boarding School in South Lampung is still not yet qualified for a nadzir. Article 6 paragraph (3) of Government Regulation No. 28 of 1977, that nadzir must be registered at the Religious Affairs Office of the local sub-district for approval. This purpose is to find out the state of the relationship between one thing and another, especially causal relationships. This type of research is field research with a case study approach. Data collection is done through observation, interviews and documentation. Data wetness using source and method triangulation. The results showed that the Nadzir in the Ushuluddin Islamic Boarding School in South Lampung was legal according to Shari'ah, but not in accordance with applicable legislation. So that the management of cash waqf at the Ushuluddin Islamic Boarding School in South Lampung is legal according to the provisions of Shari'ah, but when viewed according to the applicable laws there are still some cash waqf implementations that are not appropriate.